A258 THE GLOBAL INCIDENCE OF PEPTIC ULCER DISEASE AT THE TURN OF THE 21ST CENTURY: A STUDY OF THE ORGANIZATION FOR ECONOMIC CO-OPERATION AND DEVELOPMENT (OECD). (15th March 2019) - Azhari, H; King, J A; Underwood, F; Coward, S; shah, S; Ng, S; Ho, G; Chan, C; Kaplan, G G
Abstract: Background: The incidence of peptic ulcer disease (PUD) and its complications vary worldwide and have changed over the past few decades with the identification of H. pylori and NSAIDs as major etiologic factors, as well as the marked increase in the use of PPIs. Aims: Our primary objective was to determine differences in the worldwide trends of PUD incidence starting at the turn of the 21st century. Methods: We obtained data from the Organization for Economic Co-Operation and Development (OECD) database on hospital discharges with PUD as a primary diagnosis for 35 countries from 2000 to 2015. Hospitalization rates were converted to rates per 100, 000 person-years. Joinpoint regression models were used to calculate the average annual percent change (AAPC) with 95% confidence intervals (CI) for the rate of PUD-related hospitalizations for each country from 2000 to 2015 according to 3 predefined 5-year periods: 2000–2005; 2006–2010; and 2011–2015. Temporal inflection points were also assessed. Choropleth maps were created to illustrate the differences in hospitalization rates over time by geographic location, stratified by terciles of hospitalization rates (Fig. 1). We additionally performed a random-effects meta-analysis of AAPCs to calculate an overall AAPC. Results: PUD-related hospitalization rates from OECD countries are presented in table format. The overall median hospitalization rate was 45.81 with an interquartile range (IQR) of 31.49 to 63.61 per 100, 000 person-years. Average hospitalization rates from 2011 to 2015 were highest in Eastern Europe (Lithuania: 135.16), Western Europe (Germany: 84.90), and Asia (Turkey: 80.05), while they were lowest in South America (Mexico 4.54 and Chile 14.48) and Asia (Israel 12.98). All countries demonstrated decreasing hospitalization rates except for Switzerland. Overall, hospitalization rates for PUD decreased significantly from 2000 to 2015 (Pooled AAPC = -3.9%; 95% CI: -3.3, -4.5). Conclusions: PUD-related hospitalizations are decreasing in the vast majority of OECD countries and likely reflect an overall decreasing incidence of PUD. That said, PUD-related complications continue to pose an important health issue with significant demands on health care systems. Detailed data collection and analysis which includes the different disease subtypes and complications would aid in developing improved strategies for accelerating the downward trend in PUD and its complications. Funding Agencies: None